ISLAMISASI ILMU PENGETAHUAN: KENISCAYAAN EPISTEMOLOGI UNTUK KUALITAS PENDIDIKAN LEBIH BAIK - Damanhuri; Ulum, Bahrul (Ta'dibi : Jurnal Manajemen Pendidikan Islam, 2023)
Some Muslim scholars consider that the Islamization of science is something that is utopian in nature. The reason is that science is neutral, so there is no term Islamic or non-Islamic science. In this study it was found that this opinion is too premature and shows a lack of criticality towards what is happening in contemporary science. In fact, some sciences such as humanities and natural sciences contain values that are not in accordance with Islamic teachings. Most of these sciences are conceptually secular based. That is, there has been a separation between science and religion. Western domination that influenced the development of modern epistemology has made science far from spiritual values. The secular hegemony of Western civilization openly states that science has nothing to do with religion or God. As a result, knowledge no longer makes its possessor know God, but further distances it from God. During the heyday of Islam, classical Muslim scholars and intellectuals had 'Islamized' knowledge that came from Greek and other civilizations. The Muslims do not feel there is an epistemological problem in studying any science. So that scholars were born who mastered ulumuddin science as well as science. However, after many Islamic countries were colonized by the West, this epistemology was also eroded by secular epistemology. Islam has lost its identity as a force with an epistemological orientation that was actually well established in the classical era. Therefore, the Islamization of science today is important to do to restore the identity of Islamic science as it was in the classical period. This paper tries to analyze fairly why there is a need for the Islamization of knowledge. Islamization does not mean removing or rejecting all knowledge from the secular West. But there is a measurable selection process by adopting and adapting knowledge from the West.